Musculoskeletal ultrasound in internal medicine residency - a feasibility study - Gaurav Gulati; Richard Alweis; David George (Greater Baltimore Medical Center, 2015)
Introduction: Ultrasound has become indispensable in medicine for diagnosis and therapeutics. In Internal Medicine Residency Training Program (IMRTP), there is a deficiency of a structured, competency-based musculoskeletal ultrasound (MSKUS) training despite its growing popularity. Methods: We conducted a feasibility study for incorporating MSKUS in IMRTP and competency assessment. We recruited internal medicine residents from all training levels. Rheumatology attending with expertise in MSKUS supervised curriculum-design and patient-based assessment. A structured curriculum was developed for knee MSKUS, including training material and a pre- and post-test. An Observed Structured Clinical Exam (OSCE) was used for competency assessment. Attending evaluations and participant feedbacks were collected. Results: Fifteen residents participated and 12 completed the OSCE. The pre-post tests showed a statistically significant increase (p<0.001) for all subcomponents (anatomy, pathology, and biophysics). The residents scored high on the OSCE [8.8±1.1 (range 7-10)]. Attending evaluations for cognitive and technical skills were rated 'Excellent' (66%) and 'Good' (87%), respectively. The training program was perceived very valuable with regard to time and resources spent by residents and faculty, although some felt a need for more patient assessments. Discussion: The competency assessed with our OSCE and highly positive feedback reflects this preliminary study's importance and sets the platform for future studies of formal ultrasound training in internal medicine.